Genetic and biochemical analysis of the Archaeal Helicase Hel308 - Simmons, Emily (2019)
Completion of semi-conservative DNA replication requires various DNA repair pathways to overcome both physical and chemical obstructions to the replisome. Hel308 is a DNA repair helicase important in the maintenance of genomic stability in archaea. It is particularly important in the repair of damage that blocks replication forks, with mutants exhibiting enhanced sensitivity to inter-strand cross-links. Hel308 is a Superfamily 2 DNA helicase, conserved throughout archaea, with homologues in metazoans, including humans. It is a monomeric, ssDNA-stimulated ATPase that translocates ssDNA in the 3’ to 5’ direction, and can unwind a variety of substrates in vitro, with a preference for forked DNA. It physically interacts with the ssDNA binding protein RPA and the recombinase Rad51. However, further functional details and the translocation mechanism of Hel308 remain poorly understood.